A case study in an early childhood setting: science teaching practices and teacher perspectives - Çeviren, Ayşe Büşra. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
The purpose of this study was to describe science teaching practices and teacher’s perspective on science education in an early childhood classroom and draw a picture of early childhood teachers’ perspectives and practices at the setting on science education through a holistic view. Considering the purpose of the study descriptive case study method was employed in the study. Data were collected through lengthy observations at the early childhood classroom, which consisted of four years old children, and in-depth interviews done with seven early childhood teachers, who had experiences with four or five years old children. The data collected through observations, informal and semi-structured interviews, documents and field notes were coded in MAXQDA 11 and the themes of the study were constructed under two main themes: teacher practices and teacher perspectives. Practices of the teachers revealed that although engagement and conclusion periods of science activities were performed through active involvement of children, implementation periods involved considerable amount of teacher control. Demonstrations, explanations, authoritative question-answer session and video presentations were found to be the predominant strategies that result in teacher control. Perspectives of teachers revealed three possible considerations for this situation: lack of understanding on science education; lack of understanding on importance and goals of science education; and lack of content knowledge on science. Moreover, considerations of teachers for qualified science practices were found as being well prepared, providing science rich environments, teachers’ attitude towards science, and having children enjoy. Finally, suggestions for pre-service and in-service teacher training programs were given.
Keywords: Science -- Study and teaching (Early childhood) -- Activity programs.; Teachers -- Training of.